(untitled) (African Journal of Dairy Farming and Milk Production, 2013)
Farmers’ perception of climate change is very important for their adoption of adaptation strategies. This paper analyses dairy farmers’ perceptions of changes in rainfall patterns and its impact on dairy production in northern Malawi. Farmers’ perception was obtained through a survey and analysed using descriptive statistics, Chi-square test and a multi-nominal regression model. The accuracy of farmers’ perceptions was assessed with reference to actual rainfall data in the study area. The results revealed that majority (40%) of the respondents perceived that the amount of rainfall that the area had received over the past five years had increased. However, this was not supported by actual rainfall data. The farmers were also of the view that an increase in the amount of rainfall led to an increase in pasture production, water availability and milk production. Results from the multi-nominal regression model showed a strong relationship between milk production on one hand and water availability, and pasture production on the other. The results imply that dairy farmers in the study area do not perceive climate variability as an immediate problem and highlight the need to sensitize them about the current and projected changes in climate, their vulnerability and adaptation strategies.